Sell Side Benchmarks - KADAN, Ohad (Institutional Knowledge at Singapore Management University, 2017)
Sell-side analysts employ different benchmarks when defining their stock recommendations. For example, a ‘buy’ for some brokers means the stock is expected to outperform its peers in the same sector (“sector benchmarkers”), while for other brokers it means the stock is expected to outperform the market (“market benchmarkers”), or just some absolute return (“total benchmarkers”). We explore the validity and implications of the adoption of these different benchmarks. Analysis of the relation between analysts’ recommendations and their long-term growth and earnings forecasts suggests that analysts indeed abide by their benchmarks: Sector benchmarkers rely less on across-industry information, and focus more on ranking firms within their industries. We also find evidence that market- and sector-benchmarkers are successful in meeting or beating their benchmark returns, while total-benchmarkers are not. However, we do not find much evidence that investors react differently to recommendations based on the different benchmarks. The research carries implications for the correct understanding and interpretation of sell-side research and its investment value.